Pengaruh Model Pembelajaran SSCS (Search, Solve, Create, and Share) Berbantuan E-LKPD Terhadap Penguasaan Konsep Fisika Peserta Didik : The Effect of SSCS Learning Model (Search, Solve, Create, and Share) Assisted by E-LKPD on Students' Mastery of Physics Concepts - Yuliana, Yuliana; Zuhdi, Muhammad; Gunada, I Wayan (Prodi Fisika FKIP Unram, 2024)
This study aims to examine the effect of the SSCS (Search, Solve, Create, and Share) learning model assisted by e-LKPD on students’ mastery of physics concepts. The type of research used is quasi experiment with nonequivalent control design. The population in this study were all students of class XI SMAN 1 Lembar consisting of four classes. The sampling used purposive sampling technique and obtained students of class XI MIPA 1 as experimental class and XI MIPA 3 as control class. Data collection techniques using multiple choice tests to measure the mastery of physics concepts of students. The data obtained were analyzed using an independent t-test with the help of excel. The results showed that there was a significant difference in the mastery of physics concepts between students who used the SSCS learning model and students who used conventional learning models. This is shown from the acquisition value of tcount 2.21> ttable 1.67 so it can be concluded that there is an effect of the SSCS learning model (search, solve, create, share) assisted by e-LKPD on the mastery of physics concepts of students. Keywords: Learning Model, SSCS (Search, Solve, Create, and Share) learning model, e-LKPD, Concept Mastery.